Mental skills and tools for coaches: How and why to implement breathing techniques into your coaching - Van de Braam, M. (Coaching and Sport Science Review, 2025)
Competitive tennis places demands on players from a technical, tactical, physical and mental perspective. Relatively little information and support is available on how to navigate the mental demands of the game compared with other domains. This article aims to help coaches understand more about practical mental skills and mental tools, with a specific focus on breathing techniques to optimise well-being and performance. The research findings surrounding psychological, physiological and behavioural benefits of breathing will be explored, alongside practical coach-friendly recommendations on how to implement breathing techniques, and integrate them into coach led practice.